Synthesis of alpha,beta-unsaturated delta-lactones by vinyl acetate mediated asymmetric cross-aldol reaction of acetaldehyde: mechanistic insights - Kumar, Manjeet; Kumar, Arvind; Rizvi, Masood; Mane, Manoj; Vanka, Kumar; Taneja, Subhash C.; Shah, Bhahwal Ali (European Journal of Organic Chemistry, 2014)
A tandem asymmetric cross-aldol reaction involving the in situ generation of acetaldehyde from vinyl acetate has been developed that may resolve the challenges associated with the handling of acetaldehyde. The simple protocol, mild reaction conditions and unique harmony of an organocatalyst with a biocatalyst make this method a valuable tool for the synthesis of asymmetric beta-hydroxy aldehydes. By using this methodology we have accessed alpha,beta-unstaurated delta-lactones as well as isochromenones with high enantioselectivities from both asymmetric beta-hydroxy aldehydes and ketones. Systemic density functional theory (DFT) studies were also performed to gain mechanistic insights into the role of hydrogen bonding in the asymmetric cross-aldol reaction of acetaldehyde and in the key cis/trans isomerisation step in the synthesis of d-lactones.
Keywords: Aldol reactions; asymmetric catalysis; lactones; reaction mechanisms

Secondary interactions arrest the hemiaminal intermediate to invert the modus operandi of schiff base reaction: a route to benzoxazinones - Patel, Ketan; Deshmukh, Satej S.; Bodkhe, Dnyaneshwar; Mane, Manoj; Vanka, Kumar; Shinde, Dinesh; Rajamohanan, Pattuparambil R.; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Chikkali, Samir H. (Journal of Organic Chemistry, 2017)
Discovered by Hugo Schiff, condensation between amine and aldehyde represents one of the most ubiquitous reactions in chemistry. This classical reaction is widely used to manufacture pharmaceuticals and fine chemicals. However, the rapid and reversible formation of Schiff base prohibits formation of alternative products, of which benzoxazinones are an important class. Therefore, manipulating the reactivity of two partners to invert the course of this reaction is an elusive target. Presented here is a synthetic strategy that regulates the sequence of Schiff base reaction via weak secondary interactions. Guided by the computational models, reaction between 2,3,4,5,6-pentafluoro-benzaldehyde with 2-amino-6methylbenzoic acid revealed quantitative (99%) formation of 5-methyl-2-(perfluoropheny01,2-dihydro-4H-benzo[d][1,3]oxazin-4-one (15). Electron donating and electron withdrawing ortho-substituents on 2-aminobenzoic acid resulted in the production of benzoxazinones 936. The mode of action was tracked using low temperature NMR, IN vis spectroscopy, and isotopic (O-18) labeling experiments. These spectroscopic mechanistic investigations revealed that the hemiaminal intermediate is arrested by the hydrogen-bonding motif to yield benzoxazinone. Thus, the mechanistic investigations and DFT calculations categorically rule out the possibility of in situ imine formation followed by ring-closing, but support instead hydrogen-bond assisted ring-closing to prodrugs. This unprecedented reaction represents an interesting and competitive alternative to metal catalyzed and classical methods of preparing benzoxazinone.